Power-to-X / electricity-to-hydrogen in sector coupling: an overview & case studies - Hammam Abdelaal Hammam Soliman; Peter Badstue Jensen (Renewable Energy and Sustainable Development, 2021)
During the past couple of years, Power-to-X-to-Power has been a research and development focal point within the field of renewable energy - with thermal energy storage (TES) as an essential part of the concept. The following Paper will discuss the role of Power-to-X-to-Power in different applications such as; 1) The retrofitting of Coal-fired Power Plants (CPP), 2) Synergy with Wind Energy business, and 3) Hydrogen and e-fuel production. In order to validate the retrofitting concept, a proposed case of a potential CPP in Denmark with an average installed steam turbine generation (STG) capacity of 400 MWe is presented. In addition to the demonstration of how to apply the Power-to-X-to-Power concept to retrofit CPPs, the solution proposed also covers utilization of surplus energy generated from renewable sources such as wind and solar. Moreover, the Paper aims to explore the techno-economical opportunities regarding the hydrogen and e-fuel production.   Received: 29 July 2021 Accepted: 07 October 2021 Published: 15 November 2021